Effect of Information Communication and Technology Use and Its Implications To Firm Performance In SME - Masyhuri Masyhuri; Elivia Niadianti; Syahrul Nur Rizky; Nurhajati Nurhajati (IQTISHODUNA, 2021)
Research on firm performance during the Covid-19 pandemic, especially in SMEs, is important because it is related to efforts to survive in uncertain conditions due to the pandemic and the government's policy of restrictions that affect all businesses, both small and large. Therefore, this study aims to investigate the factors that can improve film performance, namely ICT use and as an update from previous research we add the innovation variable as a mediation. This research was conducted on SMEs in Malang City by involving as many as 179 samples after validating the answers to the questionnaire. Questionnaires were distributed through google forms which were distributed directly to respondents. The data is collected and then tested for validity and reliability so that the data used is of high quality. After testing the quality of the data, it is continued with hypothesis testing which is carried out using the boothstrapping method using the Smartpls 3.0 application. The results showed that ICT use had a significant effect on firm performance. Furthermore, innovation did not succeed in mediating the effect of ICT use on firm performance.